The monkey and the wrench : essays into contemporary poetics - Biddinger, Mary.; Gallaher, John, 1965- (Akron, Ohio : University of Akron Press, 2011)
The Monkey and the Wrench: Essays into Contemporary Poetics takes a snapshot of a moving target: the ever-shifting conversation about today's poetry. The ten essays in this collection offer reflections and insights, practical advice for craft matters, and provocative points of departure for those who read and write poetry. This series seeks to further the discussion of poetics in America and beyond, and to showcase the ideas of writers and critics with varied sensibilities. The first volume in the Akron Series in Contemporary Poetics, The Monkey & the Wrench, explores the debate over hybrid aesthetics, confronts the topic of contemporary rhyme, and ventures into the realm of persona and the mystical poem. This volume is ideal for both the classroom and the nightstand, for the poet's desk and the critic's bookshelf. Series editors Mary Biddinger and John Gallaher have assembled an eclectic collection that welcomes the reader into the conversation, while documenting the seismic activity of today's poetry world.
Introduction / Mary Biddinger and John Gallaher -- The discursive situation of poetry / Robert Archambeau -- The moves : common maneuvers in contemporary poetry / Elisa Gabbert -- An aesthetics of accumulation : on the contemporary litany / Michael Dumanis -- Cornucopia, or, contemporary American rhyme / Stephen Burt -- I am one of an infinite number of monkeys named Shakespeare, or, why I don't own this language / Benjamin Paloff -- Persona and the mystical poem / Elizabeth Robinson -- A wilderness of monkeys / David Kirby -- Hybrid aesthetics and its discontents / Arielle Greenberg [and others] -- Response to hybrid aesthetics and its discontents / Cole Swensen -- Goodbye, goodbye, goodbye : notes on the ends of poems / Joy Katz.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Poetics -- History -- 20th century; Poetics -- History -- 21st century; American poetry -- 20th century -- History and criticism; American poetry -- 21st century -- History and criticism; Poétique -- Histoire -- 20e siècle.; Poétique -- Histoire -- 21e siècle.; Poésie américaine -- 20e siècle -- Histoire et critique; LITERARY CRITICISM -- Poetry; LITERARY CRITICISM -- General; American poetry; Poetics; 1900-2099; Criticism, interpretation, etc; History